Impact of Land Use Change and Land Management on Irrigation Water Supply in Northern Java Coast - Suria Darma Tarigan; Rudolf Kristian Tukayo (UNIVERSITY OF LAMPUNG, 2013)
In Indonesia, paddy irrigation covers an area of 7,230,183 ha. Ten percent (10%) of those area or 797,971 ha were supplied by reservoirs. As many as 237,790 ha (30%) of those area supplied by reservoirs are situated downstream of Citarum Watershed called Northern Java Coast Irrigation Area or Pantura. Therefore, Citarum watershed is one of the most important watershed in Indonesia. Citarum is also categorized as one of most degraded watershed in Java. The study aimed to evaluate influence of land use change on irrigation water supply in Citarum watershed and land management strategies to reduce the impact. Tremendous land use change occurred in the past ten years in Citarum watershed. Settlement areas increases more than a double during 2000 to 2009 (81,686 ha to 176,442 ha) and forest area decreased from 71,750 ha to 9,899 ha in the same time period. Land use change influences irrigation water supply through 2 factors: a) decreasing storage capacity of watershed (hydrologic functions) for dry season, and b) decreasing storage capacity of reservoirs due to the sedimentation. Change of Citarum watershed hydrologic function was analyzed using 24 years’ time series discharge data (1984-2008) in combination with rainfall data from 2000 to 2008. Due to the land use change in this time period, discharge tend to decrease despite of increasing trendof rainfall. As a result irrigation area decreased 9,355 ha during wet season and 10,170 ha during dry season in the last ten years. Another threat for sustainability of water irrigation supply is reservoir sedimentation. Sedimentation rate in the past 10 years has reduced upper Citarum reservoir (Saguling) half-life period (½ capacity sedimented) from 294 to 28 years. If proper land management strategies be carried out, the half-life period of Saguling reservoir can be extended up to 86,4 yearsKeywords: Citarum watershed, improved land management, irrigation water supply, land use change, sedimentation [How to Cite: Tarigan SD and RK Tukayo. 2013.Impact of Land Use Change and Land Management on Irrigation Water Supply in Northern Java Coast. JTrop Soils 18 (2): 169-176. Doi: 10.5400/jts.2013.18.2.169][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.169]REFERENCESAsdak. 2004. Hidrologi dan Pengelolaan Daerah Aliran Sungai. Gadjah Mada University Press. Yogyakarta (in Indonesian).BBWSC [Balai Besar Wilayah Sungai Citarum]. 2011. Peta Informasi Citarum 2011. Direktorat Jenderal Sumber Daya Air Departemen Pekerjaan Umum (in Indonesian).Bols PL. 1978. Iso Erodents Map of Java Madura. Technical Assistant Project ATA 105. Soil Research Institute, Bogor, Indonesia. 39 ppBPDAS [Balai Pengelolaan Daerah Aliran Sungai] Citarum Ciliwung. 2008a. Pengelolaan DAS Terpadu – DAS Citarum (Buku I: Laporan utama). BPDAS Citarum Ciliwung, Ditjen RLPS Dephut. Bogor (in Indonesian).BPDAS [Balai Pengelolaan Daerah Aliran Sungai] Citarum Ciliwung. 2008b. Pengelolaan DAS Terpadu – DAS Citarum (Buku II: Data dan Informasi). BPDAS Citarum-Ciliwung, Ditjen RLPS Dephut. Bogor (in Indonesian).Bruijnzeel LA. 2004. Hydrological functions of tropical forests: Not seeing the soil for the trees? Agric Ecosyst Environ 104: 185-228.Cita. 2012. Dua puluh dua (22) Hotspost in the Citarum River Basin. www.citarum.org. Accesed on 10 October 2012.ICWRM [Integrated Citarum Water Resources Management]. 2012. Atlas Pengelolaan Sumberdaya Air Terpadu Wilayah Sungai Citarum. Cooperation between ADB and Bappenas (in Indonesian). Kimwaga RJ, F Bukirwa, N Banadda, UG Walic, I Nhapi and DA Mashauri. 2012. Modelling the impact of land use changes on sediment loading into lakeVictoria using SWAT model: A Case of Simiyu Catchment Tanzania. Open Environ Eng J 5: 66-76.Legowo S, KI Hadihardaja and Azmeri. 2009. Estimation of bank erosion due to reservoir operation in cascade (Case Study: Citarum Cascade Reservoir). ITB J Eng Sci. 41: 148-166.Perum Jasa Tirta II. 2001. Pengalaman Mengelola Bendungan Besar Waduk Ir. H. Djuanda. Perum Jasa Tirta II. Jatiluhur (in Indonesian).Shi ZH, L Ai, NF Fang and HD Zhu. 2012. Modeling the impacts of integrated small watershed management on soil erosion and sediment delivery: A case study in the Three Gorges Area, China. J Hydrol 438: 156-167.Tukayo RK. 2011. Evaluasi perubahan penggunaan lahan DAS Citarum dan dampaknya terhadap suplai air irigasi. [Thesis]. Institut Pertanian Bogor (in Indonesian).Verhaeghe RJ, B. Adriaanse and SD Tarigan. 2010. Assessment of erosion sensitivity and watershed conservation interventions for Upper Citarum basin. TA 7189-INO: Institutional Strengthening for Integrated Water Resources Management (IWRM). 6Ci’s River Basin Territory, Component B2: Spatial planning.Wang G, H Jiang, Z Hu, L Wang and W Yue. 2012. Evaluating the effect of land use changes on soil erosion and sediment yield using a grid-based distributed modelling approach. Hydrol Processes 23: 35790-3592.Yan B., NF Fang, PC Zhang and ZH She. 2013. Impacts of land use change on watershed stream flow and sediment yield: An assessment using hydrologic modelling and partial least squares regression. J Hydrol 484: 26-37.Yang H H, O Jaafar, A El-Shafie and S Mastura, 2011. Impact of land-use changes toward base-flow regime in Lui and Langkat Dengkil sub-basin. Int J Phys Sci 6: 4690-4976. Zheng H, L Zhang, R Zhu, C Liu, Y Sato and Y Fukushima, 2009. Responses of streamflow to climate and land surface change in the headwaters of the Yellow River Basin. Water Resour Res 45 (W00A19). doi: 10.1029/2007WR006665.